THE IMPACT OF NEW TARGETING METHODS IN THE CANCER THERAPY - AL-MASHHADANI, ZAKARIYA; NASER, RUA A.; ZALZALA, MUNAF H. (International Journal of Applied Pharmaceutics, 2019)
Rapid development has achieved in treating tumor to stop malignant cell growth and metastasis in the past decade. Numerous researches have emerged to increase potency and efficacy with novel methods for drug delivery. The main objective of this literature review was to illustrate the impact of current new targeting methods to other previous delivering systems to select the most appropriate method in cancer therapy. This review first gave a brief summary of cancer structure and highlighted the main roles of targeting systems. Different types of delivering systems have been addressed in this literature review with focusing on the latest carrier derived from malarial protein. The remarkable advantages and main limitations of the later have been also discussed. PubMed and Science Direct were the main search engines that have been used as information sources to prepare this review. Articles related to cancer targeting system, active and passive processes, current nanoparticles, antibody carriers, and current novel cancer carriers were used as sources in this review. Important points from many references published in the last decade (2008-2018) were selected and included. Several targeting methods were introduced to enhance the efficacy and tolerability of the toxic drug by active and passive processes, but there is still no conclusive carrier without certain drawbacks. A combination of targeting methods probably shows the most appropriate choice for increasing selectivity and safety of anticancer drugs via reducing the concentration of carriers used.